Implications of Implementation of Agriculture Asset Accounting Standards in Plantation Subsector Companies - Nurul Hasanah Uswati Dewi; Annisa Mirah Fitria Manggabarani (Jurnal Akuntansi dan Perpajakan, 2022)
The existence of business potential in agriculture has also contributed to the movement of digital economy trends, which has created a platform that can connect stakeholders in the agricultural sector. The availability of information through the platform requires financial reports that are guided by the applicable Financial Accounting Standards. PSAK 69 is an agricultural accounting standard that adopts IAS 41, which regulates accounting rules for the process of biological growth and transformation in plants and animals, up to the yield of the process. PSAK 69 became effective on January 1, 2018. This study aims to explore the implementation of accounting standards for agricultural assets in Indonesia's plantation sector. The sample of this study consisted of 24 plantation companies and food crops. The data collection method used documentation techniques, and analyzed using the Miles and Huberman model. This study finds that all companies recognize and measure biological assets managed based on PSAK 69, and there are only a few companies that carry out full disclosure points of PSAK 69